2021
DOI: 10.18632/aging.202735
|View full text |Cite
|
Sign up to set email alerts
|

A COVID-19 risk score combining chest CT radiomics and clinical characteristics to differentiate COVID-19 pneumonia from other viral pneumonias

Abstract: With the continued transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) throughout the world, identification of highly suspected COVID-19 patients remains an urgent priority. In this study, we developed and validated COVID-19 risk scores to identify patients with COVID-19. In this study, for patient-wise analysis, three signatures, including the risk score using radiomic features only, the risk score using clinical factors only, and the risk score combining radiomic features and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Thin black line hypothesizes that all patients are non-severe COVID-19. The calculation of net benefit was performed by subtracting the proportion of false positive from proportion of true positive in all patients, weighting with the relative harm of giving up treatment compared with the negative consequence of an unnecessary treatment [ 24 ]. The calculation of relative harm was performed by (Pt/(1Pt)), Pt is the threshold probability, where the expected benefit of treatment is equal to the expected benefit of avoiding treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Thin black line hypothesizes that all patients are non-severe COVID-19. The calculation of net benefit was performed by subtracting the proportion of false positive from proportion of true positive in all patients, weighting with the relative harm of giving up treatment compared with the negative consequence of an unnecessary treatment [ 24 ]. The calculation of relative harm was performed by (Pt/(1Pt)), Pt is the threshold probability, where the expected benefit of treatment is equal to the expected benefit of avoiding treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al included influenza A virus, influenza B virus, respiratory syncytial virus, parainfluenza virus, adenovirus, SARS coronavirus, Epstein–Barr virus, measles virus, or other viruses from nasopharyngeal swabs or bronchoalveolar lavage fluid ( 20 ). Chen et al included influenza virus-induced, adenovirus-induced, syncytial virus-induced, and cytomegalovirus-induced pneumonias ( 21 ). Although their studies showed that the radiomics model was an effective predictive tool to distinguish COVID-19 from other viral pneumonias (with AUC 0.807–0.888), the different types of viral pneumonia had different CT findings, which is a potential confounding factor for further comparison.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that radiomics was a valuable tool to help radiologists distinguish COVID-19 from influenza virus pneumonia. The nomogram had been widely applied to predict clinical diseases, such as the differentiation of benign and malignant cancers, cancer recurrence, and lymph node metastasis (22)(23)(24), and it was also commonly used in COVID-19 pneumonia diagnosis (20,21). In our research, the radiomics nomogram was also developed to predict COVID-19 pneumonia and aimed to illustrate the relationship between Radscore and the risk of COVID-19 pneumonia graphically.…”
Section: Discussionmentioning
confidence: 99%
“…This work was supported by the Coronavirus disease 2019 (COVID-19) emergency plan project of Anqing (2020Z1003). compared with the negative consequence of an unnecessary treatment [24]. The calculation of relative harm was performed by (Pt/(1-Pt)), Pt is the threshold probability, where the expected bene t of treatment is equal to the expected bene t of avoiding treatment.…”
Section: Ethics Approval and Consent To Participatementioning
confidence: 99%
“…The use of multi-task Unet network, which could segment the lesion or lung abnormalities related to COVID-19 automatically, increased the potential value of the radiomics nomogram in evaluating the clinical condition of patients with COVID-19.Previous studies [18,19,24] have demonstrated that CT-based radiomics as a superior tool for screening potential new cases of COVID-19, and had a good prediction on discriminating COVID-19 and non-COVID-19 pneumonia or other types of viral pneumonia. Mei et al[24] used CT-based radiomics achieved an AUC of 0.92 and had equal sensitivity as compared to a senior radiologist when applied to a group of 279 cases, CT-based radiomics can be severed as a rapid method for screening COVID-19 patients. Huang et al[19] summarized 154 patients with viral pneumonia (including 65 cases of in uenza pneumonia and 89 cases of COVID-19) to develop a CT-based radiomics model, the results showed radiomics model had a satisfactory performance in distinguishing in uenza pneumonia and COVID-19.…”
mentioning
confidence: 99%